SOLUTION CONSTRUCTION OF A PARABOLIC INITIAL-BOUNDARY VALUE PROBLEM FOR DIFFERENT REGRESSION MODELS AT THE LOWER BODY BOUNDARY - Chernukha, Olha; Bilushchak, Yurii; Chuchvara, Anastasiia; Bilushchak, Halyna (Collection of scientific papers «ΛΌГOΣ», 2025)
A parabolic initial-boundary value problem in a layer with experimental data for the sought function on the lower boundary is formulated and solved. The general solution is specified for different types of regression models.